Kidney ischemia and reperfunsion syndrome: effect of lidocaine and local postconditioning - YAMAKI,IGOR NAGAI (2016)
ABSTRACT Objective: to evaluate the effects of blocking the regulation of vascular tone on the ischemia and reperfusion syndrome in rats through the use of lidocaine in the postconditioning technique. Methods: we randomized 35 rats into seven groups of five animals: Group 1- Control; Group 2- Ischemia and Reperfusion; Group 3- Ischemia, Reperfusion and Saline; Group 4- Ischemic Postconditioning; Group 5- Ischemic Postconditioning and Saline; Group 6- Lidocaine; Group 7- Ischemic Postconditioning and Lidocaine. Except for the control group, all the others were submitted to renal ischemia for 30 minutes. In postconditioning groups, we performed ischemia and reperfusion cycles of five minutes each, applied right after the main ischemia. In saline and lidocaine groups, we instilled the substances at a rate of two drops per minute. To compare the groups, we measured serum levels of urea and creatinine and also held renal histopathology. Results: The postconditioning and postconditioning + lidocaine groups showed a decrease in urea and creatinine values. The lidocaine group showed only a reduction in creatinine values. In histopathology, only the groups submitted to ischemic postconditioning had decreased degree of tubular necrosis. Conclusion: Lidocaine did not block the effects of postconditioning on renal ischemia reperfusion syndrome, and conferred better glomerular protection when applied in conjunction with ischemic postconditioning.